POLA PENERAPAN AUTHENTIC ASSESMENT PADA MADRASAH ALIYAH NEGERI DI KABUPATEN PIDIE - ACEH - Hadini, Hadini; Imamuddin, M.; Nafiar; Nurbayani (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2024)
The implementation of authentic assessment in the field has not yet been fully optimized. Teachers at madrasahs still face difficulties in planning and carrying out authentic assessments. This research aims to: first, analyze the implementation of cognitive domain evaluation; second, analyze the implementation of affective domain evaluation; and third, analyze the implementation of psychomotor domain evaluation. The study was conducted at Madrasah Aliyah Negeri within the Pidie District, Aceh. This research employs a qualitative approach, using interviews as the data collection technique. The findings of the study reveal several key points: first, the implementation of cognitive domain evaluation in Madrasah Aliyah is carried out with a 100% score, utilizing essay tests at 43% and objective tests at 57%. Second, the use of instruments for the affective aspect by teachers is at 57%, which is considered moderate. Third, the use of instruments for the psychomotor aspect by teachers is at 43%, which is considered low.